Pengembangan Sumber Daya Manusia dalam Lembaga Pendidikan Islam - Neka, Gusti; Eka Putri, Sri Wahyuni; Jamilus, Jamilus (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2025)
The development of human resources (HR) in Islamic educational institutions is a strategic aspect that determines the success of institutions in achieving high-quality and competitive Islamic education. This study aims to analyze the urgency, normative foundations, strategies, success factors, and development models of HR relevant to the challenges of globalization and digitalization in education. The method used is a library research approach with descriptive-analytical analysis of primary and secondary sources related to Islamic educational management. The findings reveal that HR development has strong theological foundations in the Qur’an and Hadith, emphasizing professionalism (itqan), trustworthiness (amanah), and the pursuit of knowledge. Effective strategies include competency-based planning, continuous training, Islamic leadership, educational digitalization, and evaluation rooted in Islamic values. Success is influenced by individual motivation, organizational culture, policy support, and technological innovation. The ideal HR development model integrates education and training, coaching mentoring, competency-based approaches, and digital innovation. Therefore, holistic, adaptive, and value-based HR development will strengthen the existence of Islamic educational institutions amid modern global challenges.